Autoimmune encephalitis as an increasingly recognised cause of non-convulsive status epilepticus: A retrospective, multicentre evaluation of patient characteristics and electroencephalography (EEG) results - Mitchell, James W. (2020)
Purpose: Status epilepticus (SE) is a severe condition of unrelenting seizures requiring urgent identification and treatment. SE may be unprovoked, occurring in someone with epilepsy, or may be provoked by acute intracranial disease or metabolic derangement. Increasingly encephalitis, particularly autoimmune types, is reported to cause refractory seizures. Whilst convulsive SE is readily identified, non-convulsive SE (NCSE) can be difficult to identify clinically, and electroencephalography (EEG) is required. Therefore, it is critical to identify the key clinical features associated with NCSE on EEG to inform future use of EEG. Methods: We conducted a multicentre, retrospective analysis of EEG requests from four general and one specialist neurology hospital in the Northwest of England (2015-2018). Cases were identified from EEG requests for patients with suspected NCSE or other indications such as encephalopathy. We compared demographic and clinical characteristics between EEG-confirmed cases of NCSE and a randomly selected sample of negative controls. Results: 358 EEGs were reviewed, and 8 positive cases of NCSE were identified. Epilepsy was identified as the aetiology in 2 of these cases, and autoimmune encephalitis another 2 cases (one patient with N-methyl-d-aspartate receptor antibodies and another with voltage gated potassium channel antibodies). Previous alcohol excess (p = 0.005) and subtle motor signs (p = 0.047) on examination were observed more frequently in patients with NCSE compared to controls. Conclusion: Physicians should have a low threshold for urgent EEG in patients with suspected or previous encephalitis, especially if autoimmunity is suspected or subtle motor signs are present.